Acute thrombocytopenia after De-Nol. Issue 7 (July 1989) - Beckingham, I J; Baird, G; Kesteven, P J
Abstract : We describe a case of severe acute thrombocytopenia in a 72 year old man treated with De-Nol for erosive biliary gastritis.